Responses of cochlear nucleus neurons to harmonic and mistuned complex tones - Sinex, Donal G. (2007)
Preliminary measurements of the representation in the cochlear nucleus (CN) of harmonic tones, harmonic tones with mistuned components, and double harmonic tones are reported. These data indicate that, unlike auditory nerve fibers and IC neurons, neurons in the CN may exhibit one of several qualitatively-different response patterns when stimulated with mistuned tones. Primarylike neurons synchronized their discharges to 2–3 individual stimulus components, much like auditory nerve fibers do. Chopper neurons tended to respond with the periodicity of envelopes produced by interactions between adjacent stimulus components but exhibited little or no response synchronized to individual stimulus components. A small proportion of CN neurons exhibited complex slowly-modulated discharge patterns similar to those that are commonly observed in the inferior colliculus (IC). The patterns obtained from CN neurons with different pure-tone discharge patterns were generally consistent with expectations based on previous studies with other stimuli. The measurements provided additional insight into the hierarchical processing stages that result in the highly patterned responses of IC neurons to harmonic and mistuned tones.